Root Canal Treatment Failure: A Brief Review - Tiwari, Isha; Govind, Shashirekha (Journal of Biomedical and Pharmaceutical Research, 2024)
Root Canal Treatment (RCT) is a pivotal dental procedure that offers a chance to salvage teeth marred by infection or damage. This article delves into the complexities of RCT failures, examining the intricate reasons behind such occurrences. Despite its high success rate, RCT can face challenges, leading to complications and patient dissatisfaction. In this comprehensive exploration, we dissect the multifaceted causes of RCT failures, including incomplete removal of infected tissue, inadequate cleaning and shaping, poor restoration, undetected canals, fractured instruments, and external damage. Understanding these factors is indispensable for both dental professionals and patients. Incomplete removal of infected tissue, even in minute quantities, can provide a breeding ground for bacteria, resulting in reinfection. Inadequate cleaning and shaping of the root canals might leave debris behind, causing persistent infections. Restorations, a critical step post-RCT, demand precision; any ill-fitted or damaged restoration can lead to leakage, permitting bacterial ingress. The complexity of tooth anatomy occasionally conceals additional canals, which, if left untreated, can be a source of reinfection. Moreover, fractured instruments, a rare yet challenging scenario, can harbour bacteria if not managed meticulously. External damage, whether from trauma or fractures post-RCT, threatens the treated tooth’s integrity. KEYWORD: RCT Failure, Endodontics, Root canal Therapy, Treatment Outcomes, Dental Microbiology.